Study team perspectives on a multisite randomized clinical trial with underserved rural populations: A mixed methods feasibility analysis - Kristina L. Foster; Sarah Sanders; Christi A. Madden; Lacy Malloch; Amy Swango-Wilson; Barbara Jandasek; Maryam Y. Garza; Jaime Baldner; Erin Dawley; Timothy VanWagoner; Jerome Philip Saul; Ann M. Davis (PLoS ONE, 2025)
Although the literature on clinical trial methodology is quite robust, the voices of study staff as key influencers of this process are lacking, particularly for rural and underserved pediatric clinical trials. Using qualitative and quantitative (i.e., survey) methodology, the purpose of the current study was to gather information from study investigators and staff who served on one of the initial multi-state trials in the IDeA States Pediatric Clinical Trials Network (ISPCTN) regarding barriers and facilitators of conducting this rural clinical trial. Quantitative analysis indicated most study investigators and staff who responded (55%) were neutral about the various recruitment methods. Qualitative analyses identified 6 relevant themes: 1) Participant families felt overwhelmed with study procedures, 2) Incentives are important and should be given in a timely fashion to child as well as adult participants, 3) A personal connection is key to engagement and retention, 4) Specific recruitment materials and methods are preferred including family friendly consent forms and advertisements that clearly explain study procedures and clear expectations, 5) There was enthusiasm for the intervention and ideas for consideration in implementing future interventions of this type, and 6) Staff expressed enthusiasm for working in rural areas with rural participants and appreciated the unique aspects of working with this population. This paper provides valuable insight into the operational feasibility of a large, multi-site behavioral intervention trial and outlines lessons learned from study personnel with actionable tips for improving recruitment, retention, and other study procedures. These staff are open to various recruitment methods, and are enthusiastic about working with underserved, rural families. They report that they believe families can be overwhelmed by study procedures, and that a personal connection with families can facilitate study conduct.